Environmental Performance, Governance Mechanisms, and Carbon Emission Disclosure: Moderating Role of Leverage - Fanji Farman; Erpi Rahman; Ina Nusuki; Dini Wahjoe Hapsari; Dudi Pratomo (AIBPM Publisher, 2026)
Rising demand for environmental transparency has encouraged companies to improve carbon emission disclosure (CED) in sustainability reporting. However, in Indonesia, evidence on the role of corporate governance and sector-specific factors remains limited and inconsistent. This study examines the effects of environmental performance, institutional ownership, and independent commissioners on CED, with leverage as a moderating variable, among Basic Materials, Industrial, and Consumer Cyclicals firms listed on the Indonesia Stock Exchange (IDX) during 2021–2024. Using panel data regression with the Random Effect Model (REM) on 35 companies and 140 observations, the results show that environmental performance positively and significantly affects CED (? = 0.028, p = 0.039). Institutional ownership and independent commissioners do not show significant effects (p = 0.431 and p = 0.474, respectively). Leverage and all interaction terms are also non-significant, indicating that capital structure does not moderate the examined relationships in this context. These findings suggest that substantive environmental performance remains the primary driver of carbon disclosure transparency among high-emission sector firms in Indonesia.